2018
DOI: 10.1038/s41467-018-03988-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory inputs modulate respiration-related rhythmic activity in the prefrontal cortex and freezing behavior

Abstract: Respiration and airflow through the nasal cavity are known to be correlated with rhythmic neural activity in the central nervous system. Here we show in rodents that during conditioned fear-induced freezing behavior, mice breathe at a steady rate (~4 Hz), which is correlated with a predominant 4-Hz oscillation in the prelimbic prefrontal cortex (plPFC), a structure critical for expression of conditioned fear behaviors. We demonstrate anatomical and functional connections between the olfactory pathway and plPFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
146
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 59 publications
33
146
1
Order By: Relevance
“…This was supported by our finding that strong correlations of BFCNREG and auditory population activities in a specific task phase was predictive of mouse performance ( Fig.6), suggesting that behavior-dependent synchronization may underlie efficient bottom-up information transfer ( Fig.8D-E). Similar to this result, careful analysis of behavior-dependent frequency coupling lead to new insight in the active sensing field by revealing behavior-dependent theta-frequency synchronization among hippocampus, respiratory and whisking circuits [69][70][71][72] and prefrontal cortex, suggesting that such theta-frequency binding might be a rather general mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…This was supported by our finding that strong correlations of BFCNREG and auditory population activities in a specific task phase was predictive of mouse performance ( Fig.6), suggesting that behavior-dependent synchronization may underlie efficient bottom-up information transfer ( Fig.8D-E). Similar to this result, careful analysis of behavior-dependent frequency coupling lead to new insight in the active sensing field by revealing behavior-dependent theta-frequency synchronization among hippocampus, respiratory and whisking circuits [69][70][71][72] and prefrontal cortex, suggesting that such theta-frequency binding might be a rather general mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, circular distribution analysis of the phase differences between the OB and the neocortical electrodes exhibits phase differences other than 0° or 180° (Figure S2), suggesting that CRPs were not a result of volume conduction from the OB (Moberly et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1e, the coherence between respiration and ECoG that is observed during nasal respiration in W drops during mouth breathing (two-tailed t test, p = .0001). Finally, circular distribution analysis of the phase differences between the OB and the neocortical electrodes exhibits phase differences other than 0° or 180° ( Figure S2), suggesting that CRPs were not a result of volume conduction from the OB (Moberly et al, 2018). Figure 2a shows two examples of sleep to W transitions.…”
Section: Cortical Respiratory Potentials Are Present During Wakefulmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, this slow oscillation is distinct from the theta rhythm and predicts the onset and offset of freezing. Interestingly, recent work has shown that freezing-related 4Hz oscillation in the mPFC was correlated with the animal's respiratory rate, and that disruption of olfactory inputs to the mPFC significantly reduces the 4-Hz oscillation in the mPFC (Moberly et al, 2018). These data bring further support to the growing body of evidence showing that in addition to its impact on olfactory regions (for a review see Buonviso et al, 2006), nasal respiration also entrains oscillations in widespread brain regions including those involved in the fear network like the mPFC and amygdala (for a review see .…”
Section: Introductionmentioning
confidence: 99%